Industrial applications of silica-based gas adsorbents - Chan, Kit Hie; Kamarudin, Khairul Sozana Nor; Chieng, Yu Yuan; Hamdan, Halimaton; Mat, Hanapi (2005)
The emergence of silica-based gas adsorbents as nanoporous materials has created a new field of research subject in the chemistry world. This paper reviews the evolution of silica-based gas adsorbents from microporous region to mesoporous region with the main interest in the zeolites, M41S family and silica aerogel. An overview of the synthesis and modification of those adsorbents will be enumerated. Further reviews are focused on the industrial applications of the silica-based adsorbents both in current demands and future prospects with the aim to highlight the potential applications of those adsorbents in the near future.